Providing online weight management in Primary Care: a mixed methods process evaluation of healthcare practitioners' experiences of using and supporting patients using POWeR - Smith, E; Bradbury, K; Scott, L; Steele, M; Little, P; Yardley, L (BioMed Central, 2017)
Background An online weight management intervention (POWeR+) combined with a small amount of primary care healthcare practitioner support is effective in helping patients to lose weight, but little is known about how practitioners interact with the POWeR+ intervention or their experiences of providing support for patients using POWeR+. The aim of this study was to explore practitioners’ usage of POWeR+ and their experiences of providing support to patients using POWeR+. Methods Set within a randomised controlled trial of POWeR+, practitioners’ usage of POWeR+ was automatically captured and a qualitative process analysis was conducted employing semi-structured telephone interviews with practitioners who provided support to patients using POWeR+. The usage analysis captured how 54 practitioners used the POWeR+ intervention. Thirteen telephone interviews explored practitioners’ experiences of using POWeR+ and providing patients with face-to-face or remote (email and telephone) support. Interview data were analysed using inductive thematic analysis. Results Usage analysis indicated that almost all practitioners engaged with POWeR+. Pages which displayed patients’ progress and allowed practitioners to email patients were used the most. Practitioners found POWeR+ straightforward and easy to use. Some practitioners preferred providing support face-to-face, which they enjoyed more than remote support. A small number of nurses found providing non-directive support using the CARe approach (Congratulate, Ask, Remind) challenging, feeling it was the opposite of their normal approach. POWeR+ enabled practitioners to raise the topic of weight loss with patients, and POWeR+ was viewed as a superior alternative to existing weight management support which was limited in most practices. Still some practitioners found it difficult to fit providing support into their busy schedules. Conclusions Overall, practitioners engaged well with POWeR+ and perceived providing patients with support whilst using POWeR+ as acceptable and feasible. CARe provides a potentially useful model for how practitioners can combine human and digital support in a cost-effective way, which could be useful for the management of other conditions. Some potential barriers to implementation were identified, which allowed modification of POWeR+. The findings suggest that implementing this cost-effective online weight management intervention in Primary Care would be feasible and acceptable to practitioners.